Nigeria : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement, and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2022)
The economy is recovering from a historic downturn thanks to policy support, rebounding oil prices and international financial assistance. Benefiting from the authorities' pro-active approach, COVID-19 infection rates and fatalities have been contained. With higher oil prices and the country entering into the 2023 Presidential election cycle, there are risks of delays in much needed fiscal and exchange rate reforms. Macroeconomic and structural policies should build confidence and ensure a robust exit from the crisis.